(untitled) (Práxis Educativa, 2022)
In this article, it is intended to think about how colonialism acts in human formation, either by restricting thought to an “ordained world” or conditioning the human being to a distancing from nature. These two situations will be problematized from a confluence between the thesis of Antônio Bispo dos Santos, Denise Ferreira da Silva and Davi Kopenawa with the intention of thinking about another world in which the human being is in harmony with the cosmos. With this, the interest is to enunciate a counter-colonialist human formation. Keywords: Confluence. Other world. Cosmophilia.